Shadows aspect of rotating black holes in the Einstein-AdS SU(N)-nonlinear sigma model - Mohsen Fathi; Yassine Sekhmani (European Physical Journal C: Particles and Fields)
Abstract Recent observations of the supermassive black holes M87* and Sgr A* by the Event Horizon Telescope (EHT) have opened new avenues for testing gravity theories through black hole shadow observables. These observations offer a means to distinguish between general relativity and modified gravity theories while providing insights into the astrophysical properties of the observed black holes. In this work, we investigate photon orbits and shadow characteristics of rotating black holes within the Einstein- $$SU(N)$$ SU ( N ) nonlinear sigma model. We first analyze the static, spherically symmetric black hole solution, focusing on its asymptotically Anti-de Sitter behavior and causal structure. The modified Newman–Janis algorithm is then applied to obtain the rotating counterpart, followed by an examination of its geometric properties, ergoregions, and causal structure. Utilizing the Lagrangian formalism, we derive the equations of motion for photons and study the resulting black hole shadow on the celestial plane. We explore the dependence of the shadow’s size and shape on the black hole parameters K and N, imposing constraints using EHT observational data for M87* and Sgr A*. Finally, we analyze the black hole’s evaporation rate under different scenarios.